Spatial Planning and Segmentation of the Land Market - Or Levkovich; Jan Rouwendal (Tinbergen Institute, 2016)
In this paper we provide evidence of segmentation of the Dutch land markets by spatial planning into three compartments referring to agricultural, industrial and residential use. We analyze transactions of ready-to-be developed land provided by the Dutch Land Register (Kadaster) and find that residential land is much more expensive than industrial land. We also compare the prices observed in these transactions with prices for agricultural land in the vicinity and find that agricultural land is much cheaper than residential and industrial land.
Keywords: R52; R21; R33; 330; land use policy; spatial planning; land prices